Health literacy of people undergoing treatment for leprosy in an endemic municipality in the Amazon region (Revista Contexto & Saúde, 2024)
Objective: To evaluate the Functional Health Literacy of people undergoing treatment for leprosy in the Amazon context. Method: Quantitative, observational, descriptive study carried out with 23 people undergoing treatment for leprosy in municipal health units and family health strategies in two administrative districts of Belém-PA, from March to May 2023. The Health Literacy Test questionnaire was used. The data was double-entered into a database in Epi-Info 7.2, processed in the Statistical Package for the Social Science 28.0 and analyzed by variance and Spearman's correlation considering the sociodemographic variables and the score obtained in the TLS. A p-value ≤ 0.05 was considered. Results: Adequate and limited literacy in males, inadequate in females and significant in browns. People with completed high school had adequate literacy and those with elementary school had inadequate literacy. Adults had adequate literacy and the elderly had inadequate literacy. There was a statistical association between functional health literacy and the level of difficulty in reading medication packaging, understanding written information, self-management and empowerment. Conclusion: The findings point to the need for health education actions that value the profile of people undergoing treatment for leprosy, as well as investment by the education sector to offer schooling to the entire population.
Keywords: Health literacy; Treatment; Leprosy